2017
DOI: 10.1038/srep40392
|View full text |Cite
|
Sign up to set email alerts
|

Independent Aftereffects of Fat and Muscle: Implications for neural encoding, body space representation, and body image disturbance

Abstract: Although research addressing body size misperception has focused on socio-cognitive processes, such as internalization of the “ideal” images of bodies in the media, the perceptual basis of this phenomenon remains largely unknown. Further, most studies focus on body size per se even though this depends on both fat and muscle mass – variables that have very different relationships with health. We tested visual adaptation as a mechanism for inducing body fat and muscle mass misperception, and assessed whether the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
65
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 49 publications
(76 citation statements)
references
References 68 publications
3
65
2
Order By: Relevance
“…Participants who were instructed to direct overt visual attention to low (high) adiposity body stimuli showed a medium‐large visual adaptation effect, such that their PSN became lower (higher) adiposity. This is in line with previous studies showing visual adaptation to low (high) adiposity bodies presented in isolation (Brooks et al, , ; Sturman et al, ; Stephen et al, ). This is also in agreement with a previous study showing that, when participants are presented with low and high adiposity adaptation stimuli simultaneously, and are allowed to view freely, the amount of time that participants spend fixating on low versus high adiposity bodies predicts the magnitude and direction of the adaptation effect (Stephen et al, ).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Participants who were instructed to direct overt visual attention to low (high) adiposity body stimuli showed a medium‐large visual adaptation effect, such that their PSN became lower (higher) adiposity. This is in line with previous studies showing visual adaptation to low (high) adiposity bodies presented in isolation (Brooks et al, , ; Sturman et al, ; Stephen et al, ). This is also in agreement with a previous study showing that, when participants are presented with low and high adiposity adaptation stimuli simultaneously, and are allowed to view freely, the amount of time that participants spend fixating on low versus high adiposity bodies predicts the magnitude and direction of the adaptation effect (Stephen et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…It has previously been shown that body size adaptation effects can be induced in both adiposity and muscle dimensions independently (Sturman et al, ). There is increasing awareness that a significant proportion of young men desire a more muscular physique (Mitchison & Mond, ), and it has recently been shown that men at high risk of muscle dysmorphia show an attentional bias toward muscular bodies (Jin et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations